(untitled) - Duaa Althobaiti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Job satisfaction is one of the important elements in an organisation where it significantly influences the overall performance. This study will examine the employees' perception of Islamic work ethics and jobs satisfaction together with the relationship between Islamic work ethics and employee job satisfaction in Saudi Arabia. The method for collecting data is quantitative method through online survey method. The research targeting the Muslims employees, both gender female and males, different nationalities, especially in Saudi Arabia. The obtained result showed that their positive employees perception of Islamic work and job satisfaction in general.